2009
DOI: 10.1093/carcin/bgp253
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin I elicits anoikis sensitization, inhibits cellular invasion and in vivo tumor formation ability of nasopharyngeal carcinoma cells

Abstract: Nasopharyngeal carcinoma (NPC) is an Asian-prevalent head and neck cancer with high invasiveness. Although several important risk factors for NPC development have been identified, there is currently no preventive strategy for NPC, even in endemic regions. Signal transducer and activator of transcription 3 (STAT3) has been implicated in NPC carcinogenesis, which may serve as a potential target for cancer prevention. Here, we examined the chemopreventive potential of Cucurbitacin I, a natural-occurring selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 51 publications
5
43
0
Order By: Relevance
“…STAT3 may also promote cancer cell invasion and metastasis through the induction of matrix metalloprateinase-2 (MMP-2) [31] and increase angiogenesis via the induction of vascular endothelial growth factor (VEGF) and hypoxia-inducible factor 1-alpha (HIF-1α) [32] . Increasing evidence has shown that the inhibition of constitutively activated STAT3 could lead to cancer cell death and tumor regression [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 may also promote cancer cell invasion and metastasis through the induction of matrix metalloprateinase-2 (MMP-2) [31] and increase angiogenesis via the induction of vascular endothelial growth factor (VEGF) and hypoxia-inducible factor 1-alpha (HIF-1α) [32] . Increasing evidence has shown that the inhibition of constitutively activated STAT3 could lead to cancer cell death and tumor regression [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…EGFR expression and STAT3 activation are elevated in NPC, and STAT3 activation is important for the invasiveness of EBV-associated NPC, which can be blocked by STAT3 inhibitor treatment (25,26). The effects of LMP1 on EGFR, STAT3 activation, and regulation of STAT3 target genes may be important factors in the development of NPC.…”
Section: Vol 85 2011 Ebv Lmp1 Activates Pkc␦ Pathways 4405mentioning
confidence: 99%
“…Cucurbitacins normally exist as glycosides and help plants to deter predators (1). It has been reported that cucurbitacins exhibit anticancer activities against different types of cancer (2)(3)(4); however, the antitumor activity of 23,24-cucurbitacin B against cervical cancer cells remains unclear. Therefore, the present study aimed to investigate the anticancer effects of 23,24-dihydrocucurbitacin B against the human HeLa cervical cancer cell line.…”
Section: Introductionmentioning
confidence: 99%